Brotherhood marketing in Andalucia: prospective analysis through the Delphi method - Cristófol-Rodríguez, Franscisco Javier; Berraquero-Rodríguez, Diego (Revista de Estudios Andaluces, 2025)
Introduction: Cofrade marketing is a recurring issue in the contemporary society in which we live. In Spain there are more than three million cofrades, so we are facing a relevant concept in its importance in the social field. Methodology: A qualitative research was carried out using the Delphi method with a panel of eight marketing experts. Results: In relation to cofrade marketing, it is found that the brotherhoods and confraternities require a more complete management. Conclusions: Cofrade marketing emerges as a discipline that shares similar elements with religious and/or faith-based marketing and marketing in non-profit organizations but with significant differences with the implementation of other tourism, cultural and heritage elements.